Uses and risks of business chatbots : guidelines for purchasers in the public and private sectors - Peitzker, Tania (Human resource management and organizational behavior collection., 2020)
This world first summary of the evolution of 2D chatbots in websites, backends of portals and social media apps, and conversationally advanced 3D mixed reality cognitive interfaces, serves several purposes. It dissects some of the best-known case studies to emerge from the past two decades of tech giants launching the best chatbot, or supposedly the smartest, intelligent virtual assistant. From Microsoft's Tay.ai to London's Eugene Goostman claim to turing test fame, from the market dominating Amazon Alexa to Gatebox's IoT innovation with its multi-cloned Japanese hologram girlfriend, this is the first ever history of bots. This book also touches on the Trump vs Clinton chatbot wars as well as the UK Labour Party's dating site stunt, including references made to Facebook Messenger bots and the impact of the Cambridge Analytica scandal. Included in the book is a hands-on checklist and guidelines in for people wanting to buy or license bots for their companies and organizations. The author also outlines the possible use cases and key issues to consider when sourcing and commissioning your first botification project, with the final chapters predicting where the future development -- and development traps -- might lie. In this easy-to-read overview, Tania Peitzker cites leading business intelligence and analyst firms' research, and takes a deeper dive into the practical challenges of chatbots, including the obstacles and triumphs experienced by business chatbots.